An Introduction to Seshat: Global History Databank. (31st December 2018) - Turchin, Peter; Whitehouse, Harvey; François, Pieter; Hoyer, Daniel; Alves, Abel; Baines, John; Baker, David; Bartkowiak, Marta; Bates, Jennifer; Bennett, James; Bidmead, Julye; Bol, Peter; et al.
Abstract : This article introduces the Seshat: Global History Databank, its potential, and its methodology. Seshat is a databank containing vast amounts of quantitative data buttressed by qualitative nuance for a large sample of historical and archaeological polities. The sample is global in scope and covers the period from the Neolithic Revolution to the Industrial Revolution. Seshat allows scholars to capture dynamic processes and to test theories about the co-evolution (or not) of social scale and complexity, agriculture, warfare, religion, and any number of such Big Questions. Seshat is rapidly becoming a massive resource for innovative cross-cultural and cross-disciplinary research. Seshat is part of a growing trend to use comparative historical data on a large scale and contributes as such to a growing consilience between the humanities and social sciences. Seshat is underpinned by a robust and transparent workflow to ensure the ever growing dataset is of high quality.